2010
DOI: 10.1351/pac-con-10-09-08
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMR in the study of partially ordered materials: Perspectives and challenges

Abstract: The development of NMR techniques applied in the last 10 years to partially oriented systems, and in particular to liquid crystals (LCs), is the object of this brief perspective. The evolution of NMR methods (i.e., new NMR pulse sequences) and the improvement of both theoretical models and mathematic tools for the analysis of NMR data (specifically, for partially ordered systems) allowed scientists to extend their research to increasingly complex materials, such as dendrimers, polymers, and membranes, and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 177 publications
(214 reference statements)
0
13
0
Order By: Relevance
“…This NMR study [5] showed also that the smA phase of the investigated de Vries smectogen has a quite high orientational order, typical of regular smectic phases; this result was also confirmed by X-ray and Raman techniques on the same smectogen. [32] In the present work, we show that a combination of different NMR techniques [33][34][35][36][37][38][39][40] can help in understanding basic molecular and conformational properties within the whole de Vries SmA mesophase and at the SmA-SmC* transition, thus adding fundamental information to discriminate among the theoretical models reported in the literature. In particular, we focus our attention to the representative de Vries smectogen 9HL, a (S)-hexyl-lactate derivative, which consists of a rigid core of three benzoate moieties and a lactate unit, and two linear alkyl chains of 6 and 9 carbon atoms respectively (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This NMR study [5] showed also that the smA phase of the investigated de Vries smectogen has a quite high orientational order, typical of regular smectic phases; this result was also confirmed by X-ray and Raman techniques on the same smectogen. [32] In the present work, we show that a combination of different NMR techniques [33][34][35][36][37][38][39][40] can help in understanding basic molecular and conformational properties within the whole de Vries SmA mesophase and at the SmA-SmC* transition, thus adding fundamental information to discriminate among the theoretical models reported in the literature. In particular, we focus our attention to the representative de Vries smectogen 9HL, a (S)-hexyl-lactate derivative, which consists of a rigid core of three benzoate moieties and a lactate unit, and two linear alkyl chains of 6 and 9 carbon atoms respectively (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of these terms is out of the scope of this brief review, and a comprehensive explanation can be found in many books and reviews on NMR of liquid crystals, such as those reported in references [3][4][5][6][7]. Figure 2 (a)).…”
Section: Nmr Basic Principles and Applications To Study Liquid Crystalsmentioning
confidence: 99%
“…Recently, 2 H T 2 measurements have been used to investigate single molecular motions, such as overall ROT in BCMs [203][204][205], and LC dendrimers [206]. Here several of these deuterium T 2 relaxtion studies of BCMs are briefly outlined.…”
Section: Bent-core and Dendritic Mesogensmentioning
confidence: 99%